Development of Hand Gesture Detection Application for Slap Mosquito Game Based on Image Processing - Rajhaga Jevanya Meliala; Nur Indah Chasanah; Jonser Steven Rajali Manik; Anggito Rangkuti Bagas Muzaqi; Syah Bintang; Endang Purnama Giri; Gema Parasti Mindara (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2024)
The development of technology with digital image processing is often utilized to solve various problems in image processing, such as facial recognition, object detection, and interaction between users. In this study, we developed an interactive hand gesture-based game titled